Optimizing Student Learning Potential through the VAK-ZA Learning Style Identification Digital Application - Astri, Zul; Fachrunnisa, Nurul; HS, Nurmadina; Nurfadhilat, Fahrul; Wanirah, A. Isa Qar'ah Nur; Bauzad, Andi Nur Anugrah (Sarana Ilmu Indonesia (salnesia), 2025)
One of the important factors that influences the success of learning is the teacher's understanding of students' learning styles. This community service activity aimed to enhance teachers’ understanding and skills in identifying students’ learning styles through the use of the digital application “VAK-ZA Learning Style Identification”. The program was conducted on August 7–8, 2025, at SMP Negeri 28 Satap Salenrang, Maros Regency, involving 18 training participants consisting of teachers and staff, as well as 179 students who installed the “VAK-ZA Learning Style Identification” application. The application was developed in two formats, namely web and APK versions, which can be used both online and offline, making it flexible for various school infrastructure conditions. The implementation of the program included the socialization of Visual, Auditory, and Kinesthetic (VAK) learning style concepts, training in using the application, mentoring for student identification practices, and follow-up discussions on integrating the results into differentiated instruction. The results showed an improvement in teachers’ knowledge of learning style concepts as well as their skills in operating the application. Based on questionnaires, 100% of participants considered the application easy to use, useful, and relevant to learning needs. The application has proven effective in accelerating the identification process of learning styles and providing applicable teaching strategy recommendations. These findings affirm that collaboration between universities and schools can produce technology-based learning innovations that have the potential to be replicated in other schools.